Soluble bridge plug with surface coating
By setting up multiple coatings on the surface of the soluble bridge plug, the problem of sealing difficulties in ultra-high temperature, ultra-high pressure and acidic environments is solved, a more efficient fracturing process is achieved, and subsequent normal production is ensured.
Patent Information
- Application Number
- CN202311245739.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-03-28
AI Technical Summary
In oil and gas well operations, existing soluble bridge plugs are difficult to effectively seal under ultra-high temperature, ultra-high pressure and acidic environments, resulting in complex fracturing process.
By providing tungsten carbide coating, quartz sand coating, zinc-aluminum alloy coating and acid-resistant resin coating on the surface of the soluble bridge plug, its wear resistance, corrosion resistance, high temperature resistance and sealing properties are enhanced.
It can effectively carry out the seating, sealing, sealing and pressure-bearing operations in ultra-high temperatures above 150°C and 70MPa high pressure environment, improve work efficiency, and ensure normal liquid discharge and production after fracturing without affecting the dissolution of the bridge plug.
Smart Images

Figure CN119712000A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of downhole tools, and in particular, relates to a soluble bridge plug with a surface coating. Background Art
[0002] At present, in the process of oil and gas well operation, soluble bridge plugs have been widely used for formation isolation. The use of bridge plugs for formation isolation can effectively achieve staged fracturing.
[0003] With the increase in the drilling depth of oil and gas wells, the requirements for soluble bridge plugs are getting higher and higher. In some areas, the tight oil reservoirs of shale oil and gas wells during operation are as high as 6000-8000m, and the depth of some blocks is even above 8000m. In addition, there are reservoir characteristics such as ultra-high temperature of 150℃-200℃ and high pressure of 70-100MPa. Due to the dense formation and extremely high rupture pressure, after the bridge plug is used to isolate the layer section, before the formal fracturing, a complex fracturing process such as pre-treatment of the formation with carbon dioxide and acid is required. In this environment, higher requirements are placed on the bridge plug, which is required to have ultra-high temperature resistance, acid corrosion resistance, high pressure resistance and solubility.
[0004] Patent CN112620055A discloses a hydrochloric acid resistant soluble bridge plug and its preparation method and application. The preparation method includes the following steps: preparing a soluble bridge plug, performing micro-arc oxidation treatment on the surface of the soluble bridge plug; coating the surface of the soluble bridge plug that has been subjected to the micro-arc oxidation treatment with hydrochloric acid resistant paint; filling the gap between the slip seat and the slip teeth in the soluble bridge plug with epoxy glue, and curing the epoxy glue. The present application performs micro-arc oxidation treatment on the surface of the soluble bridge plug to form a micro-arc oxidation layer on its surface, and then seals the micropores formed after micro-arc oxidation by coating hydrochloric acid resistant paint, and fills the gap between the slip seat and the slip teeth with epoxy resin, so that the present application has hydrochloric acid resistance and can meet the needs of oil fracturing construction. Summary of the invention
[0005] In view of the technical problems mentioned above, the present invention aims to provide a soluble bridge plug with a surface coating, which can be applied to ultra-high temperature reservoirs with formation temperatures of 150°C-200°C and high pressure reservoirs with formation fracture pressures of 70-100MPa.
[0006] According to the present invention, a soluble bridge plug with a surface coating is provided, wherein any one or more of a tungsten carbide coating, a quartz sand coating, a zinc-aluminum alloy coating, and an acid-resistant resin coating is provided on the surface of the soluble bridge plug.
[0007] In a preferred embodiment, a tungsten carbide coating, a quartz sand coating, a zinc-aluminum alloy coating and an acid-resistant resin coating are sequentially provided on the surface of the soluble bridge plug from the inside to the outside.
[0008] In a preferred embodiment, a plasma arc driven by direct current is used as a heat source to heat the material mainly containing tungsten carbide to a molten or semi-molten state, and is sprayed on the surface of the soluble bridge plug at a spray speed higher than 150 m / s to form the tungsten carbide coating.
[0009] In a preferred embodiment, the thickness of the tungsten carbide coating does not exceed 0.5-1.0 mm.
[0010] In a preferred embodiment, compressed air is used as a power to spray quartz sand onto the surface of the soluble bridge plug to form a quartz sand coating.
[0011] In a preferred embodiment, the size of the quartz sand is 80-100 mesh, and the particle size of the quartz sand is 0.16-0.18 mm.
[0012] In a preferred embodiment, the thickness of the quartz sand coating is 0.2-0.4 mm.
[0013] In a preferred embodiment, an arc driven by inverter direct current is used as a heat source to ion heat a material mainly containing a zinc-aluminum alloy, and the material is sprayed on the surface of the soluble bridge plug to form a zinc-aluminum alloy coating.
[0014] In a preferred embodiment, the zinc-aluminum alloy coating has a thickness of 0 to 0.2 mm.
[0015] In a preferred embodiment, the dissolved acid-resistant resin liquid is sprayed onto the surface of the soluble bridge plug by a spray gun to form the acid-resistant resin coating, and the thickness of the acid-resistant resin coating is 0.2-0.5 mm.
[0016] Compared with the prior art, the advantages of the present application are as follows.
[0017] The present invention comprehensively applies one or more surface spraying process technologies to the soluble bridge plug to strengthen and modify the surface of the soluble bridge plug, so that the surface of the parts of the soluble bridge plug has better wear resistance, corrosion resistance, high temperature resistance and sealing properties. At the same time, the contact with the soluble bridge plug body under ultra-high temperature and acid conditions is isolated for a certain period of time, the dissolution rate of the magnesium alloy material of the soluble bridge plug body is reduced, the dissolution time of each component of the soluble bridge plug is prolonged, and the compressive capacity of the soluble bridge plug is increased in a short period of time, so that the soluble bridge plug can be set, isolated, and sealed under pressure in an acidic environment such as ultra-high temperature formation or wellbore temperature above 150°C, 70MPa high-pressure working pressure difference, and hydrochloric acid concentration of 10% or less, CO2 injection energy fracturing, etc., thereby providing safe and efficient interlayer isolation for ultra-high temperature and tight oil and gas formations that require ultra-high temperature, high pressure, and acid treatment of formations, improving work efficiency, and at the same time not affecting the normal dissolution of the soluble bridge plug after fracturing, ensuring the normal channel for drainage and production after fracturing. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The present invention will be described below with reference to the accompanying drawings.
[0019] Figure 1 A schematic diagram showing an embodiment of a soluble bridge plug according to the present invention;
[0020] Figure 2 A schematic diagram showing the structure of a soluble bridge plug provided with a coating according to the present invention is shown;
[0021] Figure 3 A schematic structural diagram of an adapter push cylinder according to the present invention is shown.
[0022] In the figure:
[0023] 1. Center tube; 101. Inner cavity; 2. Upper slip; 3. Upper anchoring tooth; 4. Upper cone; 5. Upper metal support ring; 6. Rubber cartridge; 7. Protective ring; 8. Lower metal support ring; 9. Lower cone; 10. Lower slip; 11. Lower anchoring tooth; 12. Guide shoe; 14. Adapter connecting rod; 15. Adapter push cylinder; 141. Rod-shaped part; 142. Connecting part; 143. Connecting section; 144. Transition section; 16. Dissolution channel; 17. Shear pin; 18. Sealing shear pin; 20. Coating; 61. Rubber cartridge assembly; 62. Upper anchoring assembly; 63. Lower anchoring assembly; 100. Soluble bridge plug.
[0024] In the present application, all drawings are schematic drawings, which are only used to illustrate the principles of the present invention and are not drawn according to the actual scale. DETAILED DESCRIPTION
[0025] Embodiment 1:
[0026] According to the present invention, this embodiment provides a soluble bridge plug with a surface coating, wherein any one or more of a tungsten carbide coating, a quartz sand coating, a zinc-aluminum alloy coating, and an acid-resistant resin coating is provided on the surface of the soluble bridge plug.
[0027] One or more of the above coatings are comprehensively applied on the soluble bridge plug to strengthen and modify the surface of the components of the soluble bridge plug, so that the surface of the components of the soluble bridge plug has the properties of wear resistance, corrosion resistance, high temperature resistance and sealing. At the same time, the contact with the components of the soluble bridge plug under ultra-high temperature and acid conditions is isolated for a certain period of time, the dissolution rate of the magnesium alloy material of the soluble bridge plug itself is reduced, the dissolution time of each component of the soluble bridge plug is prolonged, and the compressive capacity of the soluble bridge plug is increased in a short period of time, so that the soluble bridge plug can be set, isolated, and sealed under pressure in an acidic environment such as ultra-high temperature formation or wellbore temperature above 150°C, 70MPa high-pressure working pressure difference, and hydrochloric acid concentration of 10% or less, CO2 injection energy fracturing, etc., thereby providing safe and efficient interlayer isolation for ultra-high temperature and tight oil and gas formations that require ultra-high temperature, high pressure, and acid treatment of the formation, improving work efficiency, and at the same time not affecting the normal dissolution of the soluble bridge plug after the fracturing is completed, ensuring the normal channel for drainage and production after fracturing.
[0028] In a preferred embodiment, a tungsten carbide coating, a quartz sand coating, a zinc-aluminum alloy coating and an acid-resistant resin coating are sequentially disposed on the surface of the soluble bridge plug from the inside to the outside.
[0029] In a specific embodiment, the method for providing a tungsten carbide coating on a soluble bridge plug is as follows: a plasma arc driven by direct current is used as a heat source to heat a material mainly containing tungsten carbide to a molten or semi-molten state, and the tungsten carbide is sprayed on the surface of the soluble bridge plug by a spray gun or other means at a spray speed higher than 150 m / s to form a tungsten carbide coating.
[0030] Furthermore, in this embodiment, the thickness of the tungsten carbide coating does not exceed 0.5 to 1.0 mm.
[0031] In a specific embodiment, the method for providing a quartz sand coating on a soluble bridge plug is as follows: using compressed air as a power, using a spray gun or other means, quartz sand is sprayed onto the surface of the soluble bridge plug to form a quartz sand coating.
[0032] In a preferred embodiment, the size of the quartz sand is 80-100 mesh, and the particle size of the quartz sand is 0.16-0.18 mm.
[0033] Furthermore, in this embodiment, the thickness of the quartz sand coating is 0.2-0.4 mm.
[0034] In a specific embodiment, a method for providing a zinc-aluminum alloy coating on a soluble bridge plug is as follows: an arc driven by an inverter direct current is used as a heat source to ion heat a material mainly containing a zinc-aluminum alloy, and then the material is provided on the surface of the soluble bridge plug by spraying to form a zinc-aluminum alloy coating.
[0035] Furthermore, in this embodiment, the thickness of the zinc-aluminum alloy coating is 0-0.2 mm.
[0036] In a specific embodiment, the method for providing an acid-resistant resin coating on a soluble bridge plug is as follows: a dissolved acid-resistant resin liquid is sprayed onto the surface of the soluble bridge plug by a spray gun to form the acid-resistant resin coating.
[0037] Furthermore, in this embodiment, the thickness of the acid-resistant resin coating is 0.2-0.5 mm.
[0038] Embodiment 2:
[0039] The present invention will be described below with reference to the accompanying drawings.
[0040] It should be noted that, in the present application, the direction close to the wellhead after entering the well according to the present invention is described as "up", "front" or similar terms, while the direction away from the wellhead is described as "down", "back" or similar terms.
[0041] Figure 1 The structure of the soluble bridge plug 100 according to the present invention is shown. Figure 1 and Figure 2 As shown, the soluble bridge plug 100 includes a central tube 1, on the outer side of the central tube 1, an upper anchor assembly 62, a rubber cartridge assembly 61, a lower anchor assembly 63 and a guide shoe 12 are coaxially sleeved in sequence from top to bottom and axially abut against each other, the upper anchor assembly 62 and the lower anchor assembly 63 are connected to the central tube 1 through a sealing shear pin 18, the guide shoe 12 is fixedly connected to the central tube 1, and a coating 20 is provided on the surfaces of the central tube 1, the upper anchor assembly 62, the rubber cartridge assembly 61, the lower anchor assembly 63 and the guide shoe 12.
[0042] Specifically, the coating 20 may be any one or more of a tungsten carbide coating, a quartz sand coating, a zinc-aluminum alloy coating, and an acid-resistant resin coating.
[0043] According to the present invention, in a specific embodiment, the upper anchoring assembly 62 includes an upper cava 2 and an upper cone 4 coaxially sleeved on the center pipe 1 and adapted to each other, the upper end of the upper cava 2 is axially abutted against the center pipe 1, the upper cone 4 is connected to the center pipe 1 through a sealing shear pin 18, and the lower end of the upper cone 4 is axially abutted against the rubber cartridge assembly 61, and the lower anchoring assembly 63 includes a lower cone 9 and a lower cava 10 coaxially sleeved on the center pipe 1 and adapted to each other, the lower end of the lower cava 10 is axially abutted against the guide shoe 12, the lower cone 9 is connected to the center pipe 1 through a sealing shear pin 18, and the upper end of the lower cone 9 is axially abutted against the rubber cartridge assembly 61.
[0044] In a preferred embodiment, at least two rows of upper anchor teeth 3 are evenly distributed on the upper slip 2, and both the upper slip 2 and the upper anchor teeth 3 are made of high-strength ceramic particles. In this embodiment, the upper anchor teeth 3 use smaller high-strength ceramic particles, preferably with a size of 8×5mm or 9.5×7.5mm. Through this arrangement, the insoluble matter left in the well after dissolution is less than 1%, achieving the effect of facilitating the dissolution of the bridge plug.
[0045] In a preferred embodiment, at least four rows of lower anchor teeth 11 are evenly distributed on the lower slip 10, and both the lower slip 10 and the lower anchor teeth 11 are made of high-strength ceramic particles. In this embodiment, the lower anchor teeth 11 use smaller high-strength ceramic particles, preferably with a size of 8×5mm or 9.5×7.5mm. Through this arrangement, the insoluble matter left in the well after dissolution is less than 2%, achieving the effect of facilitating the dissolution of the bridge plug.
[0046] The rubber cylinder assembly 61 includes an upper metal support ring 5, a rubber cylinder 6 and a lower metal support ring 8 coaxially arranged on the central tube 1 from top to bottom. The upper end of the upper metal support ring 5 is axially abutted against the upper anchor assembly 62, and the lower end of the lower metal support ring 8 is axially abutted against the lower anchor assembly 63.
[0047] A protective ring 7 is provided between the upper metal support ring 5 and the rubber cylinder 6 , and between the lower metal support ring 8 and the rubber cylinder 6 .
[0048] like Figure 1 and Figure 3As shown, the lower end of the adapter push tube 15 is axially abutted against the upper slip 2, and the adapter connecting rod 14 is fixedly connected to the central pipe 1 through the shear pin 17. When the soluble bridge plug 100 needs to be set, the adapter connecting rod 14 moves upward relative to the adapter push tube 15, and the adapter connecting rod 14 drives the central pipe 1 and the guide shoe 12 to move upward relative to the adapter push tube 15 and the upper slip 2, so that the upper slip 2, the upper cone 4, the upper metal support ring 5, the rubber tube 6, the protective ring 7, the lower metal support ring 8, the lower cone 9, and the lower slip 10 are mutually axially compressed to achieve radial expansion, thereby achieving setting. After the setting is completed, the adapter connecting rod 14 continues to move upward relative to the adapter push tube 15 to cut the shear pin 17, thereby completing the release.
[0049] According to the present invention, a plasma arc driven by direct current is first used as a heat source to heat a material containing tungsten carbide as a main body to a molten or semi-molten state, and then sprayed at a spray speed of more than 150 m / s onto the surfaces of the central tube 1, upper slip 2, upper cone 4, rubber cylinder 6, lower cone 9, lower slip 10 and guide shoe 12 of the pre-treated soluble bridge plug 100, thereby forming a tungsten carbide coating with a thickness of no more than 0.5 to 1.0 mm. Under this setting, the speed of the sprayed particles is high, the coating is dense, the bonding strength is high, and the sprayed material is not easily oxidized.
[0050] By setting the tungsten carbide coating in this way, the ultra-high temperature characteristics are utilized to facilitate the spraying of materials containing tungsten carbide as the main body. The spraying particle speed is high, the coating is dense, the bonding strength is high, and the tungsten carbide coating finally formed is not easy to oxidize.
[0051] After the tungsten carbide coating is set, compressed air is used as a power to form a high-speed jet beam to spray quartz sand at high speed onto the surface of the soluble bridge plug 100 to form a quartz sand coating. In a preferred embodiment, the quartz sand is mainly sprayed on the upper cone 4, the lower cone 9, the upper slip 2, the lower slip 10, the guide shoe 12 and other components of the soluble bridge plug 100. By spraying quartz sand, the appearance or shape of the surface of the soluble bridge plug 100 components can be changed. Due to the impact and cutting action of quartz sand on the surface of the workpiece, the surface of the workpiece obtains a certain degree of cleanliness and different roughness, so that the mechanical properties of the surface of the soluble bridge plug 100 components are improved, thereby improving the fatigue resistance of the workpiece, increasing the adhesion between it and the coating, and extending the durability of each coating.
[0052] The size of the quartz sand is not larger than 80 mesh and not smaller than 100 mesh. In a preferred embodiment, the size of the quartz sand is 80 mesh high-purity quartz sand, and the particle size is controlled between 0.16 and 0.18 mm. The main components of the quartz sand are SiO2 (99.5 to 99.9% by weight), a small amount of Al2O3 (less than 0.001% by weight), Fe2O3 (less than 0.001% by weight) and other trace components.
[0053] In a preferred embodiment, the spraying thickness of the quartz sand coating is controlled at 0.2-0.4 mm.
[0054] After the quartz sand coating is set, an arc driven by an inverter DC power is used as a heat source to perform ion heating on the material mainly containing zinc-aluminum alloy, and is sprayed at high speed onto the surfaces of the pretreated soluble bridge plug 100's center tube 1, upper slip 2, upper cone 4, lower cone 9, lower slip 10 and guide shoe 12 to form a zinc-aluminum alloy coating.
[0055] By setting the zinc-aluminum alloy coating in this way, the zinc-aluminum alloy is subjected to the direct thermal effect of the high-temperature arc, and the thermal energy and kinetic energy of the particles are relatively high, thereby being able to obtain a higher bonding strength (more than twice that of flame spraying) and the coating's own strength. The zinc-aluminum alloy coating is denser and has a lower oxide content. After spraying, it can exhibit self-adhesive properties, and its bonding strength can reach 25 to 50 MPa.
[0056] Furthermore, the thickness of the zinc-aluminum alloy coating is controlled within 0.2 mm.
[0057] After the zinc-aluminum alloy coating is set, the dissolved acid-resistant resin liquid is dispersed into uniform and fine droplets by a spray gun with the help of atmospheric low-pressure gas pressure, and sprayed on the surface of the soluble bridge plug 100 to form an acid-resistant resin coating. In another embodiment, the acid-resistant resin coating can also be set by electrostatic spraying.
[0058] In a preferred embodiment, the acid-resistant resin coating is provided on the surface of the upper slip 2 and the lower slip 10, and the thickness is set to 0.2-0.5 mm.
[0059] In summary, through the arrangement of the coating 20 of this embodiment, the substrate surface can have the properties of wear resistance, corrosion resistance, high temperature oxidation resistance, electrical insulation, heat insulation, radiation protection, friction reduction and sealing. Among them, the tungsten carbide coating, quartz sand coating and zinc-aluminum alloy coating can improve the acid resistance of the soluble bridge plug 100, and the acid-resistant resin coating can protect the upper slip 2 and the lower slip 10 from reacting with the well fluid within 12 to 24 hours. After 12 to 24 hours, the acid-resistant resin coating falls off, and the upper slip 2 and the lower slip 10 react quickly with the well fluid, thereby providing a safe and efficient interlayer isolation for ultra-high temperature and dense layers that require ultra-high temperature, high pressure, and acid treatment of the formation, improving work efficiency, while not affecting the normal dissolution of the soluble bridge plug after the fracturing is completed, ensuring the normal channel for drainage and production after fracturing.
[0060] In the description of the present invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0061] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0062] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0063] Finally, it should be noted that the above are only preferred embodiments of the present invention and do not constitute any limitation to the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments or to replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principles of the present invention shall be included in the protection scope of the present invention.
Claims
1. A soluble bridge plug with a surface coating, characterized in that: Any one or more of tungsten carbide coating, quartz sand coating, zinc-aluminum alloy coating and acid-resistant resin coating is arranged on the surface of the soluble bridge plug.
2. The soluble bridge plug with a surface coating according to claim 1, characterized in that: A tungsten carbide coating, a quartz sand coating, a zinc-aluminum alloy coating and an acid-resistant resin coating are sequentially arranged on the surface of the soluble bridge plug from the inside to the outside.
3. The soluble bridge plug with a surface coating according to claim 1 or 2, characterized in that: A plasma arc driven by direct current is used as a heat source to heat a material mainly containing tungsten carbide to a molten or semi-molten state, and is sprayed on the surface of the soluble bridge plug at a spray speed higher than 150 m / s to form the tungsten carbide coating.
4. The soluble bridge plug with a surface coating according to claim 1 or 2, characterized in that: The thickness of the tungsten carbide coating is 0.5-1.0 mm.
5. The soluble bridge plug with a surface coating according to claim 1 or 2, characterized in that: Using compressed air as the power, quartz sand is sprayed onto the surface of the soluble bridge plug to form a quartz sand coating.
6. The soluble bridge plug with surface coating according to claim 5, characterized in that: The size of the quartz sand is 80-100 meshes, and the particle size of the quartz sand is 0.16-0.18 mm.
7. The soluble bridge plug with surface coating according to claim 5, characterized in that: The thickness of the quartz sand coating is 0.2-0.4 mm.
8. The soluble bridge plug with a surface coating according to claim 1 or 2, characterized in that: An arc driven by inverter direct current is used as a heat source to perform ion heating on a material containing a zinc-aluminum alloy as a main body, and the material is sprayed on the surface of the soluble bridge plug to form a zinc-aluminum alloy coating.
9. The soluble bridge plug with surface coating according to claim 8, characterized in that: The thickness of the zinc-aluminum alloy coating is 0-0.2 mm.
10. The soluble bridge plug with a surface coating according to claim 1 or 2, characterized in that: The dissolved acid-resistant resin liquid is sprayed onto the surface of the soluble bridge plug by a spray gun to form the acid-resistant resin coating, and the thickness of the acid-resistant resin coating is 0.2-0.5 mm.
Citation Information
Patent Citations
Hydrochloric acid-resistant soluble bridge plug and preparation method and application thereof
CN112620055A
Cited By
High-strength nano hybrid soluble bridge plug as well as preparation method and application thereof
CN120830475A